2010
DOI: 10.1021/pr1000016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversification of Peptide Toxins from the Tarantula Haplopelma hainanum (Ornithoctonus hainana) Venom Based on Transcriptomic, Peptidomic, and Genomic Analyses

Abstract: The tarantula Haplopelma hainanum (Ornithoctonus hainana) is a very venomous spider found widely in the hilly areas of Hainan province in southern China. Its venom contains a variety of toxic components with different pharmacological properties. In the present study, we used a venomic strategy for high-throughput identification of tarantula-venom peptides from H. hainanum. This strategy includes three different approaches: (i) transcriptomics, that is, EST-based cloning and PCR-based cloning plus DNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 66 publications
3
64
1
9
Order By: Relevance
“…Their studies demonstrated that the molecular weight distribution was bimodal in the 55 tarantula venoms, with the majority of peptides in the 3000-5000 Da mass range, and a second less pronounced group in the 6500-8500 Da range (Escoubas et al, 2006). Similar results were also obtained in our previous studies of venoms from Chinese tarantula spiders, such as Ornithoctonus hainana (Tang et al, 2010) and Chilobrachys jingzhao (Liao et al, 2007).…”
Section: Rp-hplc and Maldi-tof-ms Analysis Of The Venomssupporting
confidence: 84%
“…Their studies demonstrated that the molecular weight distribution was bimodal in the 55 tarantula venoms, with the majority of peptides in the 3000-5000 Da mass range, and a second less pronounced group in the 6500-8500 Da range (Escoubas et al, 2006). Similar results were also obtained in our previous studies of venoms from Chinese tarantula spiders, such as Ornithoctonus hainana (Tang et al, 2010) and Chilobrachys jingzhao (Liao et al, 2007).…”
Section: Rp-hplc and Maldi-tof-ms Analysis Of The Venomssupporting
confidence: 84%
“…A search of the recently published genome of the velvet spider Stegodyphus mimosarum (Araneomorphae) (Sanggaard et al, 2014), revealed an ITP/CHH-like gene (Genbank: AZAQ01021694.1) containing an unusually large intron ($9.7 kb) in the same position within the mature peptide as in S. maritima. Moreover, unlike araneomorph spiders (Krapcho et al, 1995), mygalomorphs appear to express intronless toxin genes Pineda et al, 2012;Tang et al, 2010), possibly indicating an inability to splice transcripts expressed in the toxin-producing regions of the venom gland.…”
Section: Figure 5 Timeline Of Chh/itp and Hand Toxin Recruitmentsmentioning
confidence: 99%
“…Remarkably, some of these peptides develop a dual function; that is, they have the ability to act as serine protease inhibitors and potassium channel blockers. The classical architecture of Kunitz-type peptides includes a short N-terminal 3 10 -helix, a C-terminal α-helix, and three strands of antiparallel β-structure, stabilized by three disulfide bridges linked as I-V, II-IV, and III-V (Vassilevski et al 2009;Tang et al 2010). …”
Section: Comparative Data In Spider Venom Gland Transcriptomesmentioning
confidence: 99%
“…There are several reports concerning the description of sodium toxin precursors (NaTx precursors) based on analyses of cDNA from spider venom glands (Satake et al 2004;Jiang et al 2008a;Tang et al 2010). The molecular organization of such precursors (amino acid sequences deduced from cDNA) has been following the general prepropeptide architecture, which is submitted to post-translational processes in order to produce the mature toxin (Figs.…”
Section: Transcripts Of Spider Peptide Toxins Acting On Sodium Ion Chmentioning
confidence: 99%